Reference values of normal abdominal aortic areas in Chinese population measured by contrast-enhanced computed tomography - Wang, Xiang; Jin, Shasha; Wang, Qing; Liu, Jiawei; Li, Fei; Chu, Haiwei; Zheng, Dexing; Zhang, Xiaolong; Ding, Jianrong; Pan, Jingli; Zhao, Wenjun (Frontiers in Cardiovascular Medicine, 2022)
ABSTRACT Objective: To generate reference values of the normal areas of abdominal aorta at various levels among Chinese people and to explore the factors that may promote the expansion of the abdominal aorta. Methods: The areas of normal abdominal aortas were gauged at various levels based on inner-to-inner measurement in 1066 Chinese adult patients (>18 years) without abdominal aortic disease. The areas of subphrenic abdominal, suprarenal abdominal, infrarenal abdominal and distal abdominal aortas were measured. The demographic and clinical characteristics were collected into a specifically designed electronic database. Multivariable linear regression was used to analyze the potential risk factors promoting the expansion of abdominal aorta. Results: In males, the median areas of subphrenic abdominal aorta, suprarenal abdominal aorta, infrarenal abdominal aorta, and distal abdominal aorta were 412.1mm2, 308.0mm2, 242.2mm2 and 202.2mm2 respectively. In females, the median areas of subphrenic abdominal aorta, suprarenal abdominal aorta, infrarenal abdominal aorta, and distal abdominal aorta were 327.7mm2, 243.4mm2, 185.4mm2 and 159.6mm2 respectively. The areas of abdominal aorta at different levels were larger in males than in females and were increased with age. Multiple linear stepwise regression analysis showed that the subphrenic abdominal aortic area was significantly related to age (β=0.544, p<0.001), sex (β=0.359, p<0.001) and hypertension (β=0.107, p<0.001). Suprarenal abdominal aortic area was related to age (β=0.398, p<0.001), sex (β=0.383, p<0.001), history of smoking (β=0.074, p=0.005) and hypertension (β=0.111, p<0.001). Infrarenal abdominal aortic area was correlated with age (β=0.420, p<0.001), sex (β=0.407, p<0.001) and history of smoking (β=0.055, p=0.036). Distal abdominal aortic area was correlated with age (β=0.463, p<0.001), sex (β=0.253, p<0.001) and hypertension (β=0.073, p=0.013). Conclusions: The abdominal aortic areas at different levels were larger in males than in females. Aging, hypertension and smoking prompt the expansion of abdominal aorta.